2019
DOI: 10.1002/jmri.26602
|View full text |Cite
|
Sign up to set email alerts
|

MRI as a diagnostic biomarker for differentiating primary central nervous system lymphoma from glioblastoma: A systematic review and meta‐analysis

Abstract: Background Accurate preoperative differentiation of primary central nervous system lymphoma (PCNSL) and glioblastoma is clinically crucial because the treatment strategies differ substantially. Purpose To evaluate the diagnostic performance of MRI for differentiating PCNSL from glioblastoma. Study Type Systematic review and meta‐analysis. Subjects Ovid‐MEDLINE and EMBASE databases were searched to find relevant original articles up to November 25, 2018. The search term combined synonyms for "lymphoma," "gliobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 46 publications
(367 reference statements)
1
43
0
Order By: Relevance
“…IVIM-DWI is a non-invasive technique that shows superiority in reflecting tumor cellularity and perfusion without requiring a contrast agent. It has already been applied in the differentiation of lung nodules ( 29 ), thyroid nodules ( 30 ), and breast ( 31 ) and brain tumors ( 32 ) with good diagnostic performance. To our best knowledge, no prostate study with a large sample size has been reported to determine the value of IVIM to quantitatively distinguish PCa from non-cancerous tissues and identify the tumor Gleason grades, in the background of IVIM becoming a research hotspot in whole-body tumors.…”
Section: Discussionmentioning
confidence: 99%
“…IVIM-DWI is a non-invasive technique that shows superiority in reflecting tumor cellularity and perfusion without requiring a contrast agent. It has already been applied in the differentiation of lung nodules ( 29 ), thyroid nodules ( 30 ), and breast ( 31 ) and brain tumors ( 32 ) with good diagnostic performance. To our best knowledge, no prostate study with a large sample size has been reported to determine the value of IVIM to quantitatively distinguish PCa from non-cancerous tissues and identify the tumor Gleason grades, in the background of IVIM becoming a research hotspot in whole-body tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) generally enables the noninvasive differentiation of typical PCNSL from GBM and advanced MRI techniques, such as dynamic contrastenhanced imaging, arterial spin labeling, magnetic resonance spectroscopy, and dynamic susceptibility-weighted contrastenhanced imaging, have been helpful in the differentiation of more complex cases. 8 However, extra expense and time are needed to perform advanced MRI techniques and these are generally not performed in routine clinical practice. 9 Conventional multiparametric-MRI (MP-MRI) including contrastenhanced T 1 -weighted imaging (CE-T 1 WI), fluid-attenuation inversion recovery (FLAIR), and diffusion-weighted imaging (DWI) are almost always performed.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first systematic review aiming at summarizing the role of diffusion MR imaging metrics in predicting survival in GBM patients. To date, systematic studies exploring diffusion metrics applied to GBM patients aimed at evaluating the power of DWI and DTI for differentiating GBM from brain metastasis or PCNSL, or from lower grade gliomas [ 32 , 33 , 88 ]. However, analysis of survival outcomes was out of the purpose of these works.…”
Section: Discussionmentioning
confidence: 99%